PRESERVATIVE EFFECT OF GINGER (ZINGIBER OFFICINALE) PASTE ON FRESH NILE TILAPIA, OREOCHROMIS NILOTICUS AT ROOM TEMPERATURE - Alhassan, E. H; Akongyuure, D. N; Dandi, S. O; Tamakloe, H. (UDS International Journal of Development, 2023)
Fish begin to degrade the moment they are removed from the water. It requires extensive post-harvest processing to extend its shelf life and maintain its quality. Freezing, smoking, canning, sun-drying, pickling, and salting are the most common methods of preserving fish. The ability of fresh Oreochromis niloticus (Nile tilapia), a popular fish food in Ghana, to be preserved by ginger (Zingiber officinale) paste was investigated. Fresh fish samples were collected from the Bontanga reservoir's landing site and were divided into two; the ginger paste group and untreated group (control) kept at room temperature in a laboratory environment. During storage, fish samples from both the ginger-treated and control groups were subjected to daily physical inspection, proximate analysis, and microbiological quality testing. After the ginger treatment, the fish had a three-day longer shelf life. The fresh fish that had not been treated (the control) had spoiled by the end of the second day, showing signs of severe physical deterioration and maggot infestation in the flesh. Microbial research also revealed that all treated samples had a lower mean microbial population than untreated samples. In contrast to 10.50 x 105 cfu/cm2 for the treated sample, the total Escherichia coli (EC) count for the untreated sample was 70.25 x 105 cfu/cm2. This demonstrates that the ginger paste gradually slowed microorganism growth in the treated samples. The study found that ginger has bactericidal and anti-spoilage properties against conditions and microbes that cause fish to spoil. Future research could alter the concentration, lengthen the study period, and include different fish species.Keywords: Tilapia, Ginger, Microbes, Preservation